Struggle Values Analysis In Novel “Kami Bukan Sarjana Kertas” By J.S Khairen (2019) - Manuputty, Peter; Ayani, Ayani; Patty, Shania (INTERACTION: Jurnal Pendidikan Bahasa, 2021)
The purpose of this study are (1) to describe the value of struggle in novel Kami (Bukan) Sarjana Kertas by J.S. Khairen (2) describes the value benefits of internal struggle in novels Kami (Bukan) Sarjana Kertas. The method in this research is using descriptive method analytic by reading, taking notes, and analyzing every sentence in the novel which contains elements of literary sociology. The data source of this research came from novel Kami (Bukan) Sarjana Kertas by J.S.Khairen. The novel itself is produced from events social life of the community and the author himself. Therefore, the novel contains a variety the dynamics of life that occur in the community. This research is aimed at describes the sociological aspects of literature in the novel Kami (Bukan) Sarjana Kertas J.S. Khairen. The form of data from this research is in the form of sentences in the novel that contain elements of the values of struggle. The results of this novel research are to describe (1) the value of the willing sacrifice (2) the value of cooperation (3) the value of patience and never give up (4) the value of unity (5) the value hard work. The benefits are (1) the value of self-sacrifice (2) the value of cooperation (3) the value of patience and never give up (4) the benefit of the value of unity (5) the benefit of the value of hard work.